Ectodysplasin A Is Increased in Non-Alcoholic Fatty Liver Disease, But Is Not Associated With Type 2 Diabetes - Bayliss, Jacqueline; Ooi, Geraldine J.; De Nardo, William; Shah, Yazmin Johari Halim; Montgomery, Magdalene K.; McLean, Catriona; Kemp, William; Roberts, Stuart K.; Brown, Wendy A.; Burton, Paul R.; Watt, Matthew J. (Frontiers in Endocrinology, 2021)
Ectodysplasin A (EDA) was recently identified as a liver-secreted protein that is increased in the liver and plasma of obese mice and causes skeletal muscle insulin resistance. We assessed if liver and plasma EDA is associated with worsening non-alcoholic fatty liver disease (NAFLD) in obese patients and evaluated plasma EDA as a biomarker for NAFLD. Using a cross-sectional study in a public hospital, patients with a body mass index >30 kg/m2 (n=152) underwent liver biopsy for histopathology assessment and fasting liver EDA mRNA. Fasting plasma EDA levels were also assessed. Non-alcoholic fatty liver (NAFL) was defined as >5% hepatic steatosis and nonalcoholic steatohepatitis (NASH) as NAFLD activity score ≥3. Patients were divided into three groups: No NAFLD (n=45); NAFL (n=65); and NASH (n=42). Liver EDA mRNA was increased in patients with NASH compared with No NAFLD (P=0.05), but not NAFL. Plasma EDA levels were increased in NAFL and NASH compared with No NAFLD (P=0.03). Plasma EDA was related to worsening steatosis (P=0.02) and fibrosis (P=0.04), but not inflammation or hepatocellular ballooning. ROC analysis indicates that plasma EDA is not a reliable biomarker for NAFL or NASH. Plasma EDA was not increased in patients with type 2 diabetes and did not correlate with insulin resistance. Together, we show that plasma EDA is increased in NAFL and NASH, is related to worsening steatosis and fibrosis but is not a reliable biomarker for NASH. Circulating EDA is not associated with insulin resistance in human obesity.